Adversarial image-to-image model to obtain highly detailed wind fields from mesoscale simulations in mountainous and urban areas - Milla Val, Jaime; Montañés, Carlos; Fueyo, Norberto (Jornada de Jóvenes Investigadores del I3A, 2024)
The characterisation of wind is of great interest in multiple disciplines such as city planning, pedestrian comfort and energy generation. We propose a conditional Generative Adversarial Network (cGAN), based on the Pix2Pix model [1], that can generate detailed local wind fields in areas with complex orography or an urban layout, which are comparable in level of detail to those from Computational Fluid Dynamics (CFD) simulations, from coarser Numerical Weather Prediction (NWP) data.